CORRELATION OF BODY MASS INDEX WITH MENARCHE AGE IN ELEMENTARY SCHOOL STUDENTS IN KRIAN - Icha, Icha; Dewi, Sianty; Sudewi, Ni Putu (JOURNAL OF WIDYA MEDIKA JUNIOR, 2024)
Introduction: Early menarche is increasing throughout the world, including in Indonesia. The average age of early menarche in Indonesia is less than 10 years based on the results of Riset Kesehatan Dasar or Basic Health Research 2013. Early menarche can cause stress, cardiovascular disease, and the risk of breast cancer. Early menarche can be influenced by various factors, one of which is nutritional status which can be assessed by body mass index.Objective: To determine the relationship between Body Mass Index and Menarche Age in elementary school “X” in Krian.Method: This study used a cross-sectional research design, conducted on a population of elementary school children in grades IV-VI aged 9-12 years at primary school “X” in Krian with the inclusion criteria being School Health Unit (Unit Kesehatan Sekolah or UKS) data and the exclusion criteria being having chronic diseases. Data analysis was carried out using the Spearman Correlation test.Results: 49 samples were obtained consisting of 7 people in class IV, 14 people in class V, and 28 people in class VI. From the sample, 8 children had a low BMI (16.3%), 30 children had a normal BMI (61.3%), and 11 children had a high BMI (22.5%). Meanwhile, for early menarche 6 people (12.2%), normal menarche 43 people (87.8%), and no late menarche (0%) obtained a p-value = 0.616 (p>0.05). The percentage of early menarche in obese BMIs is higher than in other BMIs with a percentage of 6.1%.Conclusion: There is no significant correlation between body mass index and age at menarche due to the small number of samples.